On the Cardinalities of Interpolating Restricted Ranges (Journal of Computational Mathematics, 1987)
The cardinalities of interpolating restricted range $R_1(m,n)$ for best rational approximation are discussed. The conditions under which the cardinality of $R_1(m,n)$ is 0 or 1 or $∞$ are established by using the results obtained in [3,4].